Stand Fast, Craig-Royston! (Volume II) - Black, William, 1841-1898 (Salt Lake City, UT : Project Gutenberg, 2013)
"Stand Fast, Craig-Royston!" by William Black is a novel written in the late 19th century. The story revolves around the characters Vincent and Maisrie Bethune, exploring themes of loyalty, artistic ambition, and the complexities of familial and romantic relationships. The narrative examines Vincent's deepening feelings for Maisrie amidst troubling circumstances surrounding her grandfather, George Bethune. The opening of the novel introduces Vincent grappling with a distressing letter from an unknown correspondent in America accusing George Bethune, Maisrie's grandfather, of misconduct in regards to a book project. Vincent wrestles with his admiration for George and the implications of this claim while trying to protect Maisrie from potential harm. As Vincent confronts the unfolding drama, he visits Maisrie to discuss these troubling rumors, revealing the emotional turmoil and protective instincts growing between them. The scene sets an atmosphere of personal conflict intertwined with themes of integrity and love as the characters navigate their relationships within a society fraught with pressures. (This is an automatically generated summary.)
Release date is 2013-05-17
Produced by Al Haines
Keywords: Grandfathers -- Fiction; Scotland -- Social life and customs -- 19th century -- Fiction; Families -- Fiction; Older people -- Fiction